Skeletal muscle transcriptome in healthy aging - Tumasian, Robert A.; Harish, Abhinav; Kundu, Gautam; Yang, Jen-Hao; Ubaida-Mohien, Ceereena; Gonzalez-Freire, Marta; Kaileh, Mary; Zukley, Linda M.; Chia, Chee W.; Lyashkov, Alexey; Wood, William H.; Piao, Yulan; et al. (Nature communications, 2021)
Age-associated changes in gene expression in skeletal muscle of healthy individuals reflect accumulation of damage and compensatory adaptations to preserve tissue integrity. To characterize these changes, RNA was extracted and sequenced from muscle biopsies collected from 53 healthy individuals (22–83 years old) of the GESTALT study of the National Institute on Aging–NIH. Expression levels of 57,205 protein-coding and non-coding RNAs were studied as a function of aging by linear and negative binomial regression models. From both models, 1134 RNAs changed significantly with age. The most differentially abundant mRNAs encoded proteins implicated in several age-related processes, including cellular senescence, insulin signaling, and myogenesis. Specific mRNA isoforms that changed significantly with age in skeletal muscle were enriched for proteins involved in oxidative phosphorylation and adipogenesis. Our study establishes a detailed framework of the global transcriptome and mRNA isoforms that govern muscle damage and homeostasis with age. As human skeletal muscle ages, gene expression programs change and reflect damage accumulation and homeostatic resilience mechanisms. Here, the authors present a detailed framework of the global transcriptome that characterizes skeletal muscle during aging in healthy individuals.